In Vitro Release of Interferon-Gamma from Peripheral Blood Lymphocytes in Cutaneous Adverse Drug Reactions. (6th June 2012) - Goldberg, Ilan; Hanson, Meital; Chodick, Gabriel; Shirazi, Idit; Brenner, Sarah
Abstract : Background . Cutaneous drug reactions are common but diagnostically challenging due to phenotypic heterogeneity and simultaneous exposure to multiple drugs. These limitations prompted the development of diagnostic tests. Aims . To evaluate the performance of an in vitro assay measuring interferon-gamma release from patients' lymphocytes in the presence of causative drugs for the diagnosis of drug reactions. Methods . Mononuclear cells derived from patients were incubated with and without suspected drugs, and increment of interferon-gamma levels was measured by ELISA. We performed a telephonic survey to evaluate the effect of stopping the drugs incriminated by the assay on cutaneous manifestations. Results . We assessed 272 patients who used 1035 medications. When assessed against the questionnaire data collected at least 6 months after stopping the causative drug, sensitivity was found to be 83.61% and specificity 92.67%. Likelihood ratio for a positive test is 11.40 and for a negative test 0.18. Positive predictive value is 75.37% and negative predictive value is 95.47%. The test was found to perform significantly better in females and in older patients. Conclusions . Interferon-gamma release test is a useful adjunct tool in the diagnosis of cutaneous drug reactions.